Role of landscape context in Toxoplasma gondii infection of invasive definitive and intermediate hosts on a World Heritage Island. (December 2022) - Okada, Sono; Shoshi, Yuki; Takashima, Yasuhiro; Sanjoba, Chizu; Watari, Yuya; Miyashita, Tadashi
Abstract: Free-ranging cats are invasive species threatening biodiversity worldwide. They may also impose an environmental risk to humans and livestock through the transmission of zoonotic diseases. We investigated antibody levels against Toxoplasma gondii in free-ranging cats and black rats (definitive and representative intermediate hosts) by ELISA and determined their relationships with landscape environmental factors on Tokunoshima Island, Japan, the Natural World Heritage site. We found a higher seroprevalence (>70%) in both cats and black rats in landscapes where the cattle barn density was high. This was consistent with higher density of rats revealed in our trapping survey. The spatial scale of landscape factors affecting infection was broader in cats (1 km buffer radius) than in black rats (100 m buffer radius). Both cats and rats showed an increasing trend in optical density (OD) values with increasing body weight and landscape cattle barn density, suggesting that the antibody concentration increases as the chance of exposure to T. gondii in the environment increases. Thus, management actions to stop humans from feeding cats and to control rat populations without using cats are both necessary to reduce the human health risk as well as to conserve endangered species on the island. Graphical abstract: Image 1 Highlights: High seroprevalence of T. gondii was found in cats and black rats on an island. Seroprevalence was high (>70%) in landscapes where there were many cattle barns. Antibody level in cats was lower in forests and higher around residential areas. Spatial scale of environmental factors affecting infection was broader in cats.